Chimeric analogs of human β-defensin 1 and θ-defensin disrupt pre-established bacterial biofilms. Issue 15 (1st August 2017) - Mathew, Basil; Olli, Sudar; Guru, Ankeeta; Nagaraj, Ramakrishanan
Graphical abstract: Abstract: Antibiofilm activity of several human defensin analogs that have the ability to kill planktonic bacteria, against pre-established biofilms of Escherichia coli MG1655 and Staphylococcus aureus NCTC 8530 were examined. Linear and linear fatty acylated analogs did not show any activity while disulfide constrained analogs disrupted pre-established S. aureus biofilms. Chimeric analogs of human β-defensin 1 and θ-defensin, hBTD-1 and [d ]hBTD-1 were highly active against S. aureus biofilms. Among the analogs tested, only thed -enantiomer [d ]hBTD-1 showed activity against E. coli biofilm. Our study provides insights into the structural requirements for the eradication of pre-established biofilms in defensin analogs.